Questions kids ask about faraway places - Comely, Richard; Dickie, Alison (Grolier Toronto, 1989)
Questions Kids Ask About Faraway Places answers children's curious inquiries about different countries and cultures, fostering a sense of exploration and broadening their understanding of the world.